2014
DOI: 10.1111/jgh.12460
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapy with artificial light suppresses dextran sulfate sodium‐induced colitis in a mouse model

Abstract: Artificial light phototherapy suppressed DSS-induced colitis in mice by suppression of pro-inflammatory cytokines and promotion of anti-inflammatory cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 40 publications
0
16
0
Order By: Relevance
“…35 The experimental design for both studies was similar in that the light therapy was delivered before induction of colitis. 37, 38 Both studies showed a positive effect of the light treatments on experimental IBD symptoms in this model. 37, 38 The dose of light was sufficient in one study to raise serum 25(OH)D levels but in the other was not.…”
Section: Vitamin D Uvr and Experimental Ibdmentioning
confidence: 57%
See 4 more Smart Citations
“…35 The experimental design for both studies was similar in that the light therapy was delivered before induction of colitis. 37, 38 Both studies showed a positive effect of the light treatments on experimental IBD symptoms in this model. 37, 38 The dose of light was sufficient in one study to raise serum 25(OH)D levels but in the other was not.…”
Section: Vitamin D Uvr and Experimental Ibdmentioning
confidence: 57%
“…37, 38 Both studies showed a positive effect of the light treatments on experimental IBD symptoms in this model. 37, 38 The dose of light was sufficient in one study to raise serum 25(OH)D levels but in the other was not. 37, 38 The doses of light delivered were 600mJ/cm 2 (no raise in serum 25(OH)D) on shaved mice versus 14 J/cm 2 on unshaved mice (raised serum 25(OH)D).…”
Section: Vitamin D Uvr and Experimental Ibdmentioning
confidence: 57%
See 3 more Smart Citations